Risk factors for hospital admission and length of stay for children with and without congenital anomalies: a EUROlinkCAT cohort study - Mika Gissler; Maria Loane; Joan K Morris; Ester Garne; Silvia Baldacci; Francesca Gorini; Elisa Ballardini; Marco Manfrini; Joachim Tan; Stine Kjaer Urhoj; Sonja Kiuru-Kuhlefelt; Joanne Given (BMJ Paediatrics Open)
Objective To evaluate risk factors for hospital admission and length of stay (LOS) among children with and without congenital anomalies (CAs).Design A population-based linkage cohort study including 50 353 children with major CAs and 1 259 925 children without CAs from four EUROCAT registry areas in three countries. Data on children born 1995–2014 were linked to hospital discharge databases 1995–2015. HRs and incidence rate ratios estimated risk of admission and LOS for children aged <1 and 1–4 years by birth cohort, gestational age, sex, maternal age, multiple births and maternal education. Estimates were pooled using random effects meta-analysis.Results In children <1 year, twins/triplets with CAs were 34% more likely to be admitted and had over two times the LOS compared with singletons, while twins/triplets without CAs were over two and a half times as likely to be admitted and had six times longer stays. Despite this, a higher proportion of twins/triplets with CAs were admitted compared to those without CAs (91% vs 65%) and had longer LOS (20 days vs 10). Smaller increases in risk of admission or LOS were found in boys, young mothers and low maternal education. Preterm birth was a major risk factor for admission and LOS.Conclusions While the impact of risk factors on hospital admission and LOS was generally greater in children without CAs, a higher proportion of children with CAs were admitted and had longer stays. These findings have implications for health care planning and for counselling parents regarding their child's future healthcare needs.